Laparoscopic cholecystectomy under continuous spinal anesthesia in a patient with Steinert's disease - Correia,Mariana (2016)
ABSTRACT Steinert's disease is an intrinsic disorder of the muscle with multisystem manifestations. Myotonia may affect any muscle group, is elicited by several factors and drugs used in general anesthesia like hypnotics, sedatives and opioids. Although some authors recommend the use of regional anesthesia or combined anesthesia with low doses of opioids, the safest anesthetic technique still has to be established. We performed a continuous spinal anesthesia in a patient with Steinert's disease undergoing laparoscopic cholecystectomy using 10 mg of bupivacaine 0.5% and provided ventilatory support in the perioperative period. Continuous spinal anesthesia was safely used in Steinert's disease patients but is not described for laparoscopic cholecystectomy. We reported a continuous spinal anesthesia as an appropriate technique for laparoscopic cholecystectomy and particularly valuable in Steinert's disease patients.